Highlight on Bottlenecks in Food Allergen Analysis: Detection and Quantification by Mass Spectrometry. (22nd November 2019) - Planque, Mélanie; Arnould, Thierry; Renard, Patricia; Delahaut, Philippe; Dieu, Marc; Gillard, Nathlie
Abstract: Food laboratories have developed methods for testing allergens in foods. The efficiency of qualitative and quantitative methods is of prime importance in protecting allergic populations. Unfortunately, food laboratories encounter barriers to developing efficient methods. Bottlenecks include the lack of regulatory thresholds, delays in the emergence of reference materials and guidelines, and the need to detect processed allergens. In this study, ultra-HPLC coupled to tandem MS was used to illustrate difficulties encountered in determining method performances. We measured the major influences of both processing and matrix effects on the detection of egg, milk, soy, and peanut allergens in foodstuffs. The main goals of this work were to identify difficulties that food laboratories still encounter in detecting and quantifying allergens and to sensitize researchers to them.